2021
DOI: 10.31822/jomat.2021-6-2-89
|View full text |Cite
|
Sign up to set email alerts
|

Tourist satisfaction with American continent airports

Abstract: Tourist satisfaction is very important in terms of destination loyalty as revisit and recommendation intentions. The development of airline transportation has led to an increase in the average time spent by tourists during the destination process by shortening the transportation time. The purpose of this study is to determine the spatial distribution of passenger satisfaction levels at airports in the Americas. For this purpose, data for determining tourist satisfaction has been obtained from two different pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Yavuz [45] stated in this regard that queueing times are critical for achieving overall passenger satisfaction. Moreover, queuing time is found to be one of the most influential factors on satisfaction [46,47]. Consequently, the following hypothesis is posited: Hypothesis 1 (H1).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Yavuz [45] stated in this regard that queueing times are critical for achieving overall passenger satisfaction. Moreover, queuing time is found to be one of the most influential factors on satisfaction [46,47]. Consequently, the following hypothesis is posited: Hypothesis 1 (H1).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…While in our study, compliance with distancing at the luggage belt and counters and limited availability of health messages in different languages were found to be unsatisfactory. Crowd management and queuing to control a crowd is very challenging; however, studies have shown that queuing time is a potential influencing factor for the higher satisfaction level among flight passengers [45,46]. Another research carried out among frequent flyers revealed that passengers agreed to receive complimentary sanitizer and masks, along with additional information about prevention aspects, so that they can feel safer while flying [21].…”
Section: Discussionmentioning
confidence: 99%